TEKNIK MANAJEMEN KELAS BAGI EFEKTIFITAS AKTIVITAS PEMBELAJARAN - Supardi Supardi (SOCIETY, 2013)
Teaching in a typical classroom, teachers play at least three major roles: making choises about instructional strategies, designing classroom curriculum and making employing classroom management technique. Of the three roles, classroom management is arguably the foundation. Effective teaching and learning can not take place in a poorly managed classroom. If students are disorderly and disrespectful, and no apparent rules and procedures guide behavior, chaos becames the norm. In these situstions, both teachers and students suffer. Teachers struggle to teach, and students most likely learn much less than they should. In contrast, well-managed classrooms provide an environment in which teaching and learning can flourish. But a well-managed classroom management does not just appear out of nowhere. It takes a good deal of effort to create, and the person who is most responsible it is the teacher. This article discusses some questions relating to the concept of classroom management, teacher’s role as a classroom manager, and procedure and discipline as the main aspects of classroom management including research and practice perspectives on which they are based.